Influence of silica materials on synthesis of elastomer nanocomposites: A review. (December 2020) - Najam, Mohsin; Hussain, Murid; Ali, Zulfiqar; Maafa, Ibrahim M; Akhter, Parveen; Majeed, Khaliq; Ahmed, Ashfaq; Shehzad, Nasir
At the end of 19th century, the modification of silica has brought revolution in the field of nanocomposites and gained the attention of researchers again by the development of the mesoporous silica class. Silica when used with elastomers provides distinctive characteristics merging the superior properties of inorganic fillers, such as hardness, increased thermal strength, and mechanical stability along with the processability, elasticity, and plasticity of the organic polymers. When carbon black is treated with elastomers instead of silica, it provides greater level of reinforcement because the surface of silica is polar and hydrophilic, but it has greater tendency to adsorb moisture, which affects the ionization of silanol groups. The reason behind switching to silica is adverse effects of carbon black on environment. When silica is added in greater amount, it increases the viscosity of rubbers significantly. The high viscosity causes the processing extra difficult by generating excessive wear and tear over the processing equipment. The increase in viscosity is associated with the strong interaction among the silica particles. It has also been reviewed that the use of silica as filler in elastomers was hindered as far as bifunctional organosilanes were discovered. These are referred to as surface-modifying materials and are initiators for treating silica surfaces to make the filler compatible and friendly to elastomers.